The Role of Innovative Approaches in Enhancing Security Awareness among Security Personnel in the Emirate of Sharjah: A Social Study - Bin Hadaa, Saeed; AlGharaibeh, Faker; Al-Taii, Alaa (Al-Adab Journal, 2024)
The study aimed to analyze the role of innovative security methods in enhancing the sense of security among employees of the Sharjah Police General Command. This was achieved through evaluating the implementation of innovative methods in reducing crime rates and assessing the necessity of innovation in security work. The study employed a qualitative approach, collecting data from a sample of 15 individuals working within the Sharjah Police General Command. The findings revealed several significant results: innovative methods play a prominent role in reducing both organized and petty crimes, adapting and utilizing innovative methods in security work is crucial for enhancing awareness and efficiency among police officers, and contributes to the development of effective crime-fighting strategies and public safety enhancement. Additionally, the study confirmed that the application of innovative methods has contributed to crime rate reduction, indicating a positive transformation in security management through the adoption of modern and scientific approaches. It emphasized the important role of innovative methods in crime rate reduction, achieving general deterrence, and enhancing community partnerships in the field of security and public safety.